Recollections expressed by mechanically ventilated patients of Intensive Care Unit (ICU), Hospital Universiti Kebangsaan Malaysia (HUKM) - Ho, Siew Eng; Hamidah Hassan; Sanisah Saidi; Syed Zulkfli (Penerbit UKM, 2008)
Ventilated patients who require intensive care unit (ICU) treatment may encounter unpleasant experiences. These experiences may include factual incidents and delusional memories of ICU such as dreams, hallucinations and frightening experiences. A cross sectional study using “Intensive Care Experience Questionnaire” consisted of four domains: awareness of surrounding, frightening experiences, recall of experience and satisfaction with nursing care. Forty five participants who fulfilled the inclusion criteria were recruited in this study. This study was conducted in ICU of HUKM from January to March 2006. Results showed that 20 respondents (44%) were aware of their surrounding and 31 respondents (69%) reported frightening experiences. Majority of respondents (43 respondents, 96%) reported satisfaction with the delivery of nursing care. There was positive correlation between awareness of surrounding and their abilities to recall their experiences (p<0.05). Patients’ awareness of surrounding achieved the strongest statistical significance as a contribution to the prediction of their abilities to recall their experiences with beta coefficient value of 0.353 and p<0.05. The finding of this study permits nurses to see the problems of mechanically ventilated patients through reports of unpleasant recollections by the patients themselves. Patients reported frustrations in their attempts to make their needs known. Although they are on sedation, they are aware of all unpleasant events occurring in the ICU